Central European Tourist Flows: Intraregional Patterns and Their Implications - Šauer Martin; Vystoupil Jiří; Novotná Markéta; Widawski Krzysztof (Moravian Geographical Reports, 2021)
Understanding tourist spatial behaviours is essential for strategic planning and sustainable development. Especially at the city-level, data provide implications for spatial planning and transport governance. Intraregional tourist flows to cities contributed significantly to the total volume of tourists within the Central European region before the COVID-19 pandemic outbreak. Given the challenges that urban tourism is currently facing, intraregional tourist flows could be a strategic opportunity for future growth. As a comprehensive assessment of the tourist flows at this spatial level is lacking, the paper aims to evaluate the structure of these flows and discuss the factors that influence their spatial distribution. Statistical data analysis of tourist flows to selected cities in Central Europe is evaluated by multiple linear regression. The results show that the main factors affecting the distribution of tourist flows are air connection, the attractiveness of the destination, and the size of the source market. Tourist flows within Central Europe are fundamentally affected by Germany. This market can be considered the most important source of demand for inbound tourism. Germany's national ties with Austria and Switzerland generated 47% of all trips examined. In this case, the influences of historical ties and the broader socio-economic context are evident.